2017
DOI: 10.1016/j.ebiom.2017.02.012
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Blood Plasmalogen Changes by Oral Administration of Plasmalogen in Patients with Mild Alzheimer's Disease and Mild Cognitive Impairment: A Multicenter, Randomized, Double-blind, Placebo-controlled Trial

Abstract: BackgroundPlasmalogens (Pls) reportedly decreased in postmortem brain and in the blood of patients with Alzheimer's disease (AD). Recently we showed that intraperitoneal administration of Pls improved cognitive function in experimental animals. In the present trial, we tested the efficacy of oral administration of scallop-derived purified Pls with respect to cognitive function and blood Pls changes in patients with mild AD and mild cognitive impairment (MCI).MethodsThe study was a multicenter, randomized, doub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
92
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 109 publications
(98 citation statements)
references
References 34 publications
2
92
1
3
Order By: Relevance
“…Furthermore, some clinical symptoms of PD were improved concomitantly. Beneficial effects of the same ether phospholipids ingestion were also observed in patients with AD [15]. e oral ingestion of purified ether phospholipids derived from scallop improved some cognitive functions of AD [15].…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…Furthermore, some clinical symptoms of PD were improved concomitantly. Beneficial effects of the same ether phospholipids ingestion were also observed in patients with AD [15]. e oral ingestion of purified ether phospholipids derived from scallop improved some cognitive functions of AD [15].…”
Section: Discussionmentioning
confidence: 71%
“…It is reported that plasmalogens are abundant in the brain, retina, leukocytes (immune cells), sperm, heart, and skeletal muscle in mammals [10,11]. Vinyl ether bond at the sn-1 position makes plasmalogens more susceptible to oxidative stress than corresponding ester-bonded glycerophospholipids [11][12][13][14][15]. erefore, plasmalogens may act as antioxidation and protect cells from oxidative stress [13,14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparatively, lower dose of plasmalogens (1 mg twice daily) and the labile nature of the vinyl‐ether bond might have limited the absorption of the intact molecule and might have contributed to the lack of response in terms of plasmalogen levels in the blood as well as the cognitive function (Mini Mental State Exam‐Japanese version or Welchsler Memory Scale‐Revised), except for female patients with mild AD given plasmalogen supplementation who showed a significant improvement in Welchsler Memory Scale‐Revised compared with the placebo group. The authors suggested that studies with longer duration and observation of converters from MCI to AD might be needed to evaluate the efficacy of plasmalogen supplementation because the study duration of the study might be too short [62]. The dose of plasmalogens used in this study (2 mg/day, which amounts to about 0.03 mg/kg) is an inadequate dosage in our view for elevating tissue levels.…”
Section: Human Intervention Studiesmentioning
confidence: 96%
“…6 Of note, lower levels of plasmalogens have been reported in patients with Alzheimer's disease but not in patients with other neurodegenerative disorders, suggesting plasmalogen deficiency may be a specific biomarker for Alzheimer's disease. 7,8 Lipids in breast milk are contained within milk fat globules, which consist of a trilayer membrane of polar lipids, cholesterol, enzymes, and glycoproteins surrounding a triglyceride core. 9 A study in rats demonstrated that formula supplemented with bovine milk fat globule membrane (MFGM) normalized intestinal development compared with control formula, with intestinal readouts similar to rats receiving mothers' milk.…”
mentioning
confidence: 99%